Analysis of Work Results, Attitudes and Discipline on Work Performance in the Kok Tong Medan Mass - Abdi Setiawan; Sonia Gulo (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze the influence of work results, attitudes, and discipline on employee work performance in the Kok Tong Medan Mass. In the context of increasingly fierce business competition, employee performance is a key factor in achieving company goals. The research method used is a quantitative approach with a population and the sample of this study is 33 employees. Data processing uses the SPSS Version 24 application. The data testing was carried out using classical assumption tests and hypothesis tests. Data analysis was carried out using multiple linear regression to identify the relationship between independent variables (work outcomes, attitudes, and disciplines) and dependent variables (work performance). The results of the study show that work results, attitudes, and discipline simultaneously have a significant effect on employee work performance. Partially, attitude and discipline have a more dominant influence compared to work results. The results showed that the result of X1 (Work Results) was calculated 3,206> ttable 2,490, Result X2 (Attitude) was calculated 4,029 > ttable 2,490, Result X3 (Work Discipline) calculated 2,780 >ttable 2,490 while the significant value t of each variable was also less than 0.05, then reject Ho and accept Ha. Based on the Determination Test, it can be seen that the Y Variable which means that Work performance has a Regrsi Square value of 73.0% means that this bound variable has a simultaneous effect on the independent variable, and vice versa Work Results, Attitudes, and Work Discipline have a positive and significant effect on Work Achievement in the Kok Tong Medan Mass, both partially and simultaneously. Work Discipline is the most dominant factor affecting Work Performance rather than Attitude. These findings indicate the importance of increasing positive attitudes and work discipline in order to improve employee work performance. This research is expected to contribute to the management of Kok Tong Medan Mass in formulating a more effective human resource development strategy.